New records of marsupials from the Miocene of Western Amazonia, Acre, Brazil - Narla S. Stutz; Patricia Hadler; Francisco R. Negri; Laurent Marivaux; Pierre-Olivier Antoine; François Pujos; Tiago R. Jacó; Emmanuelle M. Fontoura; Leonardo Kerber; Annie S. Hsiou; Roberto Ventura Santos; André M.V. Alvim; et al. (Acta Palaeontologica Polonica, 2023)
The Amazonian region covers a significant part of the South American continent and harbors outstanding biodiversity. However, much of its history is still unknown. This situation has begun to change with paleontological field efforts over the last decades, which have been proving that fossils can be common in this region. Despite their great current species richness and abundance in the area today, marsupials have a sparse fossil record, restricted to a few specimens from handful Cenozoic Amazonian localities. Here we present new records of fossil marsupial teeth from the Solimões Formation (lower Eocene–Pliocene), on the Juruá and Envira riverbanks (Acre, Northwestern Brazil). The localities investigated yield at least four distinct didelphid didelphimorphians at PRE 06 (Ponto Rio Envira: Marmosini ?Marmosa sp., Didelphis cf. D. solimoensis, Thylamys? colombianus, plus unidentified didelphids), and two paucituberculatans from the Juruá River localities (Ponto Rio Juruá: the palaeothentid Palaeothentinae indet. at PRJ 25 and PRJ 33’, and Abderitidae indet. from PRJ 33). In agreement with the associated mammalian faunas, most of the didelphids, except for Thylamys? colombianus from PRE 06, indicate a (?early) Late Miocene age for this locality. Conversely, the abderitid specimens found in situ at PRJ 33 would match a Middle Miocene age. The palaeothentids found at PRJ 25 and PRJ 33’ localities cannot be considered for biostratigraphic inferences, since they were found outside a stratigraphic context. Nevertheless, these paucituberculatans considerably add to our knowledge, as they are the first ever recorded in Brazilian Amazonia.